2020
DOI: 10.1667/rade-20-00100.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Fractionated Radiotherapy (GRID) Prior to Standard Neoadjuvant Conventionally Fractionated Radiotherapy for Bulky, High-Risk Soft Tissue and Osteosarcomas: Feasibility, Safety, and Promising Pathologic Response Rates

Abstract: Spatially fractionated radiotherapy (GRID) has been utilized primarily in the palliative and definitive treatment of bulky tumors. Delivered in the modern era primarily with megavoltage photon therapy, this technique offers the promise of safe dose escalation with potential immunogenic, bystander and microvasculature effects that can augment a conventionally fractionated course of radiotherapy. At the University of Maryland, an institutional standard has arisen to incorporate a single fraction of GRID radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Disease-specific series of definitively treated STS patients have been presented in abstract form 9 10 , and one outcome study 12 was recently published. These studies show high response rates, local control rates of 85-100% 9 12 and limb-sparing rate of 93% 9 in bulky (>8-10 cm) sarcomas, which overall exceed the outcomes of standard therapy [39][40][41] .…”
Section: Sfrt Clinical Trial Design Consensus Guideline For Stsmentioning
confidence: 99%
See 4 more Smart Citations
“…Disease-specific series of definitively treated STS patients have been presented in abstract form 9 10 , and one outcome study 12 was recently published. These studies show high response rates, local control rates of 85-100% 9 12 and limb-sparing rate of 93% 9 in bulky (>8-10 cm) sarcomas, which overall exceed the outcomes of standard therapy [39][40][41] .…”
Section: Sfrt Clinical Trial Design Consensus Guideline For Stsmentioning
confidence: 99%
“…Spatially fractionated radiation therapy (SFRT) is a complex concept of increasing clinical, experimental and translational interest. Pilot studies have shown unexpectedly high tumor responses to SFRT and low toxicity in bulky metastatic and primary tumors [1][2][3][4][5][6][7][8][9][10][11][12][13] . The observed enhanced tumoricidal effects of SFRT are thought to be related to the vastly inhomogeneous dose distributions 4 14 15 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations